Energy-Efficient Buildings, a step towards Sustainability in Pakistan - Usman, Hashir (International Journal of Engineering and Management Sciences, 2019)
With every passing year, energy consumption in the world is increasing drastically. Most of the energy comes from fossil fuels which are also depleting in a fast manner. Buildings consume a significant amount of energy all over the world and the demand for energy is also increasing unremittingly in buildings. Developed countries are taking profound measures in order to make buildings energy efficient and sustainable by achieving nearly zero energy stage. Pakistan is facing a serious energy crisis from the past few decades. The building sector in Pakistan deserves special attention in this regard since the energy consumption in buildings in Pakistan is feverishly high. Many types of research have been carried out in Pakistan by the United Nations and Energy Department of Pakistan in order to devise applicable methods that not only provide thermal comfort to the occupants but also make a building energy efficient. Renewable energy also plays an important role in compensating building energy demands. It is easy to achieve nearly zero energy state in a good energy efficient building if it is coupled with renewable energy sources then it will make it self-sufficient in energy demand. A survey is also carried out to determine the thermal comfort of the occupants in different types of areas. Also, solar energy analysis is also taken into account to highlight the solar power potential in Pakistan. Several recommendations have also been suggested to implement energy efficiency measures in Pakistan.